Analisis Profitabilitas terhadap Return Saham pada Indeks LQ 45 Tahun 2021 - La Sudarman; Wa Ode Ida (Jurnal Ekonomi & Bisnis, 2022)
This study aims to examine the effect of profitability (ROA, ROE and NPM) on stock returns in companies listed on the LQ 45 Index. Using survey research with qualitative descriptive methods. The sample used in the study was 45 companies listed on the LQ 45 Index in 2020. The sampling technique used census techniques, and the data analysis technique used  multiple linear analysis with the help of the SPSS version 20 software application. Based on the results of the data analysis used, it was found that partial ROA affects stock returns, ROE affects stock returns and NPM affects stock returns. Simultaneously profitability (ROA, ROE and NPM) affect stock returns. The R Square value of profitability has an effect on stock returns of 51.4% and the remaining 49.6% is influenced by other variables not included in this study.